Risk of testicular cancer in men with abnormal semen characteristics: cohort study - Jacobsen, Rune (BMJ, 2000)
OBJECTIVE: To explore the associations between semen characteristics and subsequent risk of testicular cancer. DESIGN: Cohort study. PARTICIPANTS: 32 442 men who had a semen analysis done at the Sperm Analysis Laboratory in Copenhagen during 1963-95. MAIN OUTCOME MEASURE: Standardised incidence ratios of testicular cancer compared with total population of Danish men. RESULTS: Men in couples with fertility problems were more likely to develop testicular cancer than other men (89 cases, standardised incidence ratio 1.6; 95% confidence interval 1.3 to 1.9). The risk was relatively constant with increasing time between semen analysis and cancer diagnosis. Analysis according to specific semen characteristics showed that low semen concentration (standardised incidence ratio 2.3), poor motility of the spermatozoa (2.5), and high proportion of morphologically abnormal spermatozoa (3.0) were all associated with an increased risk of testicular cancer. The only other cancer group that showed increased incidence was “peritoneum and other digestive organs” (six cases; 3.7, 1.3 to 8.0). Of these, two cases were probably and two cases were possibly extragonadal germ cell tumours. CONCLUSIONS: The results point towards the existence of common aetiological factors for low semen quality and testicular cancer. Low semen quality may also be associated with increased incidence of extragonadal germ cell tumours.